Respostas
respondido por:
36
(x - 1)2 = x2-2x+1
a=1
a=1
respondido por:
123
Para que o 1-i seja raíz de p(x) , p(1-i) deve ser nulo .
p(x) = x²-2x+a
Como p(1-i) = 0 :
p(1-i) = (1-i)² - 2.(1-i) + a
p(1-i) = 1-2i+i² - 2+2i + a
p(1-i) = 1-2i-1 - 2+2i + a
p(1-i) = -2+a
0 = -2+a
a = 2 .
p(x) = x²-2x+a
Como p(1-i) = 0 :
p(1-i) = (1-i)² - 2.(1-i) + a
p(1-i) = 1-2i+i² - 2+2i + a
p(1-i) = 1-2i-1 - 2+2i + a
p(1-i) = -2+a
0 = -2+a
a = 2 .
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás